Novel Shared Key Transfer Protocol for Secure Data Transmission in Distributed Wireless Networks - Sungheetha, Akey; R, Rajesh Sharma (Journal of Trends in Computer Science and Smart Technology, 2020)
Handling Keys in the distributed wireless network is one of the most popular options that ensures the protection of data that are transmitted under various circumstances. It even assists the setting up, reversal and the looking after of keys across diverse. So this makes it requisite to process and produce a corporate key that is secret and as well as distribute it across the network that is decentralized. This sort of key is termed as the shared key. The shared key aids in the procedures of encrypting and decrypting the information's that are to be transmitted. Multitudes of applications are developed based on the decentralized wireless network such as wireless adhoc network, mobile adhoc networks, wireless sensor networks etc. are suggested with the secret key protection to enhance the security level while transmitting data. The shared key transfer protocol (SKTP) procedure accomplishes encryption /decryption for the message to be transferred it uses a group of key and shares them across a several transmissions that takes place across the head of the cluster and the nodes in the clustered paradigm. This shared collection of keys allows the consumer to encode and decode the message that is to be conveyed for all the consumers in a group enabling a member in the cluster to work together with the other member in the group around the data discovery. So the paper aims in establishing a novel shared key transfer protocol (N-SKTP) that is dynamic in nature and practically possible to secure the information transfer across the devices in the distributed wireless network. The N-SKTP utilizes the pubic key cryptography to develop a shared key group (SKG) for the manifold transmission in the network. The investigation of the performance of the proposed protocol using the network simulator -2 experimentally demonstrates the proficiency of the N-SKTP in the distributed wireless networks with limited resources.
Keywords: Distributed Wireless Networks; Secret Keys; N-SKTP; SKG; Encryption Decryption